Isoliquiritigenin ameliorates caerulein‐induced chronic pancreatitis by inhibiting the activation of PSCs and pancreatic infiltration of macrophages - Wang, Li‐Juan (J Cell Mol Med, 2020)
Chronic pancreatitis (CP) is characterized by persistent inflammation of the pancreas that results in progressive loss of the endocrine and exocrine compartment owing to atrophy and/or replacement with fibrotic tissue. Currently, the clinical therapeutic scheme of CP is mainly symptomatic treatment including pancreatic enzyme replacement, glycaemic control and nutritional support therapy, lacking of specific therapeutic drugs for prevention and suppression of inflammation and fibrosis aggravating in CP. Here, we investigated the effect of isoliquiritigenin (ILG), a chalcone‐type dietary compound derived from licorice, on pancreatic fibrosis and inflammation in a model of caerulein‐induced murine CP, and the results indicated that ILG notably alleviated pancreatic fibrosis and infiltration of macrophages. Further in vitro studies in human pancreatic stellate cells (hPSCs) showed that ILG exerted significant inhibition on the proliferation and activation of hPSCs, which may be due to negative regulation of the ERK1/2 and JNK1/2 activities. Moreover, ILG significantly restrained the M1 polarization of macrophages (RAW 264.7) via attenuation of the NF‐κB signalling pathway, whereas the M2 polarization was hardly affected. These findings indicated that ILG might be a potential anti‐inflammatory and anti‐fibrotic therapeutic agent for CP.